Influence of musical accompaniment on the quality of strength training classes with university students - Kozlov, Alexandr V.; Budarnikov, Anatoly A. (Физическое воспитание и студенческий спорт, 2025)
The paper presents the results of the research on the development and implementation of musical accompaniment in training sessions and extra-curricular classes of strength sports (such as powerlifting, strength fitness, kettlebell lifting and others) at the Presidential Academy. It has been found out that in the educational and training processes, it is desirable that musical composition be related to the age of students, their socio-cultural characteristics, upbringing and other social factors. When choosing music for a given exercise intensity, the tempo of the musical composition should be related to the heart rate of the student during the exercise, to the part of the lesson and to the type of the lesson. When choosing music for an individual student, influence of a particular student’s personal associations should be taken into account. Musical accompaniment developed by the authors for classes and extra-curricular sessions in strength sports has been tested in practice and has made it possible to improve the quality of classes, to raise motivation and involvement of students in developing their strength qualities.